Function of Negative Imperative Sentences Found in Disney's Mulan Movie 2020 - Ni Wayan Rai Sugiartini; I Wayan Resen; Ni Made Verayanti Utami (ID Solutions, 2021)
This study was conducted to analyze the functions of negative imperative sentences found in Disney’s Mulan movie 2020. The data that used in this study taken from Disney’s Mulan movie which have been downloaded from Telegram application. This movie tells the story of a young Chinese woman who disguises herself as a male warrior in order to save her father. The data were collected through observation method by watching the movie repeatedly, taking a note and making the list of negative imperative sentences. The theory used to classify the functions of negative imperative sentence proposed by Quirk et. al (1985). There are three functions of negative imperative sentences were found in this article. First function is prohibition. It is used to forbid someone to do something. Second function is warning. It is used to warn someone to stop doing something. The last function is suggestion. It is used to give a suggestion to someone in doing something or stop doing something. Keywords— negative imperative, function, movie